(untitled) (CAHIERS MAGELLANES-NS, 2024)
This study explores the effects of osmotic stress induced by Polyethylene Glycol (PEG 6000) on chromosomal aberrations in Allium cepa L. roots. The roots were exposed to 10% and 20% PEG solutions, mimicking drought conditions. The control group exhibited healthy root growth with an average length of 12.6 ± 0.6 cm, while the 10% and 20% PEG treatments significantly reduced root lengths to 8.9 ± 1.0 cm and 6.6 ± 0.3 cm, respectively. The mitotic index decreased from 43.15% in the control group to 21.90% and 27.06% under 10% and 20% PEG treatments. Chromosomal aberrations were absent in the control group but increased with PEG concentration, showing frequencies of 0.26 in 10% PEG and 0.38 in 20% PEG treatments. Observed aberrations included chromosome breaks, anaphase bridges, disturbed metaphases, clumped chromosomes, and others. These results indicate that PEG-induced osmotic stress significantly impairs root growth, mitotic activity, and chromosomal integrity in Allium cepa. This study underscores the Allium cepa bioassay's utility in assessing environmental stress impacts on plants and provides insights into the mechanisms of stress-induced genetic damage, contributing to a better understanding of plant responses to drought conditions.